Titles support the development of coherent situation models. (7th July 2020) - Christofalos, Andriana L.; Raney, Gary E.; Daniel, Frances; Demos, Alexander P.
Abstract : Background: Research shows that providing readers with a title prior to reading a passage increases comprehension compared with reading a passage without a title. However, the specific type of comprehension that is facilitated by the presence of a title and how this relates to reading time has not been examined. We present three experiments in which we evaluated the effect of passage titles on comprehension and reading time. Methods: Participants read vague passages once or twice either with titles or without titles and answered questions after each reading that assessed surface form, textbase and situation model comprehension. Reading time was recorded for each reading of each passage. Results: When a title was absent, there was a large reduction of situation model comprehension, a small to moderate reduction in textbase comprehension and little or no reduction in surface form comprehension compared with when a title was present. The presence or absence of titles had an inconsistent effect on reading time. Conclusions: We conclude that titles provided a theme that helped readers develop a coherent situation model when reading the vague passages and that creating a situation model supports comprehension but has a smaller effect on reading time for the simple texts used here.